USULAN PENINGKATAN PERFORMA MESIN K413 BERDASARKAN ANALISIS NILAI OVERALL EQUIPMENT EFFECTIVENESS PADA DIVISI KNITTING DI PT MULIA KNITTING FACTORY - Ginting, Meriastuti; Panji Survana, I Made (Teknik dan Ilmu Komputer, 2012)
The Knitting division of PT Mulia Knitting Factory aims at improving the performance of K413 machine so that losses can be minimized. A basic parameter is required to describe the effectiveness of the machine as the first step for improvements. The parameter used was overall equipment effectiveness (OEE). The result of the calculations showed that the OEE rate of K413 machine was 68.48%. The poor rate was due to the low availability and performance ratio of the K413 machine caused by the operators that prefer to handle the new machine, the position of the K413 machine in the high flywaste area, the same maintenance schedule with the new machine, the poor quality of the material, and the lack of operators. Estimated financial losses due to this problem was 4,526,715 rupiahs per month. The new standard of OEE is set at 83,61 %. Increasing the number of operators with a clear job description, using new engine spare parts, advancing the maintenance schedule of the K413 machine, and changing the machine position can improve the OEE rate of the K413 machine.                 Keywords:   overall equipment effectiveness, availability ratio, performance ratio, quality ratio, financial loss estimation, improvement